Learning to Live Through Loss: Grief and the Mourning Process - Carolyn S. Wilken (EDIS, 2006)
FCS-2267, a 5-page fact sheet by Carolyn Wilken, is one in a series of six publications dealing with grief, death, and loss. This publication gives detailed descriptions of the stages of grief and explains how different kinds of deaths may cause different reactions. Also gives specific guidance on how to help someone who is grieving. Published by the UF Department of Family, Youth and Community Sciences, November 2006.